WeChat-Based Intervention for Chinese Immigrants With Hypertension: Development and Evaluation Study - Wen-Wen Li; Prisca Toh (JMIR Publications, 2023)
BackgroundDespite Chinese immigrants having a higher or comparable proportion of hypertension (HTN) compared to non-Hispanic White and Hispanic individuals, there are no effective technology-based intervention studies that target HTN management in Chinese immigrants in the United States. ObjectiveThe aim of this study was to develop and pilot-test the efficacy of a culturally and linguistically sensitive social media-based intervention (WeChat) for Chinese immigrants to improve blood pressure (BP) control, antihypertensive medication adherence, and self-efficacy. MethodsThe study was conducted in 2020 with a pre- and posttest design (N=20). A WeChat-based intervention was implemented using one 20-minute video presentation plus one 20-minute nurse counseling session via WeChat at the baseline, followed by 4 biweekly 20-minute nurse counseling sessions via WeChat calls. The primary outcome (BP control) and secondary outcomes, including medication adherence and self-efficacy in HTN management, were measured at baseline and at 6 months. ResultsThe participants' mean age was 68.9 (SD 10.2; range: 51-86) years. The majority of the participants were female (n=13, 65%), had a high school degree or less (n=15, 75%), were married (n=16, 80%), not religious (n=13, 65%), and not employed (n=12, 60%). The results showed that the mean baseline systolic BP was 131.43 (SD 9.61) mmHg, and the mean diastolic BP was 79.79 (SD 9.62) mmHg. The 6-month outcome showed a reduction of systolic BP (-0.74, SD 9.18 mmHg; P=.05) and diastolic BP (-0.96, SD 6.92 mmHg; P=.001). The mean score for medication adherence at baseline was 4.50 (SD 1.70), and it significantly improved to 3.65 (SD 1.18) at 6 months (reversely scored; possible range was 1-5, with 1 being the best score; P=.001). Self-efficacy in HTN management had a trend in reduction from a baseline score of 8.28 (SD 1.25) decreasing to 7.93 (SD 1.48) at 6 months, with a mean difference of 0.34 (SD 2.02), with a score of 0 indicating the lowest self-efficacy and a score of 10 indicating the highest self-efficacy. ConclusionsOur WeChat-based HTN management program showed a significant improvement in diastolic BP and medication adherence as well as a trend of reduction for systolic BP and self-efficacy in managing HTN in Chinese immigrants. Compared to the traditional health care system, the proposed WeChat-based HTN management program has a low cost and is easy to implement. Thus, further investigation is recommended to generate further results. This intervention should be tested across different regions and clinical settings to verify the findings. The long-term goal is to implement the intervention in clinical settings to help Chinese immigrants at large achieve better HTN management.